Sign Up or Sign Off: Asia’s Reluctant Engagement with the International Criminal Court - FINDLAY, Mark (Institutional Knowledge at Singapore Management University, 2014)
The International Criminal Court argues that there is a need to achieve universal ratification so that the majority of mankind will no longer remain outside the protection of the ICC. In the Asia/Pacific region there is a relatively low accession rate of nation states to the Rome Statute. This paper proposes a taxonomy of resistance to ratification in the region, recognising that in speculating on the reasons for resistance to the ratification of international criminal justice, local to the global across Asia and the Pacific, there is a risk in both over emphasising cultural and political difference while at the same time seeking universal themes at the expense of real jurisdictional peculiarities. Once this taxonomy is roughed out, then the paper in part meets the paradox that in Africa and South America, where similar features of possible resistance exist, the ratification process has been much more widespread. Why is this so?